FAKTOR – FAKTOR YANG MEMPENGARUHI PERMINTAAN DAGING BROILER DI KOTA MALANG - Ariani Trisna Murti; Sri Andika Putri (BUANA SAINS, 2018)
The research was conducted on a number of consumers who bought broiler chicken and not sold again. The number of respondents in each market amounted to 100 respondents incidental sampling. Research location was chosen with consideration because the big market is in the middle of the city, while for dinoyo market because of its location on subdistrict and reside in the residential area. The data collected are primary and secondary data. The type of this research is quantitative descriptive, that is research which describes or describe characteristic from a state or object of research done through data collecting, data analysis and interpretation result of its analysis. The research method used survey method. Data processing from the results of research conducted using Cobb-Douglas function using SPSS version 16.0. Based on the results of research conducted on broiler consumers in Malang City can be concluded that the factors that affect the level of demand for broiler meat in the city of Malang is the price of the goods themselves (broiler meat prices), price of chicken meat, beef prices, cooking oil prices, incomes per capita, education and consumer tastes.